Revitalizing Teacher Pedagogical Interaction with Students in Fiqh Learning - Akib, Akib; Joshua, Wang; Niva, Matteson; Maharjan, Kailie; Syukur, Taufik Abdillah (Al-Hijr: Journal of Adulearn World, 2024)
One of the problems in schools, especially in the subject of Islamic jurisprudence, is that many students find that when practicing they do not pay enough attention to the teacher who is teaching, this is due to a lack of teacher interaction with students, where interaction in the learning process is very necessary to make students comfortable in learning. The aim of this research is to determine the benefits of the teacher's ability to interact with students in the fiqh learning process. The research method used by the researcher is a quantitative method using an in-depth interview and survey system. The results of this research show that students are able to understand fiqh material well when teachers can interact well with students in the learning process. So researchers can conclude that interaction between teachers and students is very important in the learning process. The limitation of this research is that the researcher only focuses on good interaction between teachers and students in Fiqh learning, therefore the researcher hopes that further research can be carried out in other learning subjects.